Two new naphthalene glycosides from the seeds of Cassia obtusifolia. Issue 10 (3rd October 2019) - Pang, Xu; Li, Na-na; Yu, He-Shui; Kang, Li-Ping; Yu, Hai-Yang; Song, Xin-Bo; Fan, Guan-Wei; Han, Li-Feng
Abstract: A phytochemical study on the seeds of Cassia obtusifolia was carried out, which finally led to obtain two naphthalenes (1 and2 ), two naphthopyrans (3 and4 ) and twelve anthraquinones (5 –16 ). The structures of all compounds were established mainly by NMR and MS experiments as well as the necessary chemical evidence. Among them, 1 and2 (obtusinaphthalensides A and B) were identified to be new naphthalene glycosides. Abstract :